Checklist and molecular phylogenetics reveal three taxonomic novelties in Habenaria (Orchidaceae, Orchidoideae) from Chapada dos Veadeiros, Goiás, Brazil - Batista, João A. N.; Cruz-Lustre, Gabriela; do Vale, Aline A.; Bianchetti, Luciano B. (European Journal of Taxonomy, 2023)
A comprehensive checklist of Habenaria from Chapada dos Veadeiros, State of Goiás, was performed alongside morphologic and molecular phylogenetic studies, revealing three new taxa endemic to this region. A total of 61 taxa (59 species and two varieties) of Habenaria are recorded for Chapada dos Veadeiros, representing a two-fold increase compared to previous lists and comprising one of the greatest diversities of the genus in Brazil. Of this total, four taxa are locally endemic. Habenaria cultellifolia, until recently known only from the type collection, was rediscovered in the region after 127 years without records and represents this species’ only known extant population. Three proposed new taxa of Habenaria (H. minuticalcar J.A.N. Bat. & Bianch. sp. nov., H. proiteana J.A.N. Bat., A.A. Vale & Bianch. sp. nov., and H. lavrensis var. xanthodactyla J.A.N. Bat. & Bianch. var. nov.) are corroborated by molecular phylogenetic analyses based on nuclear and plastid markers. They are described, illustrated, tentatively assessed as threatened, and compared to phylogenetically and morphologically related species. Since some areas of this mountain range have not yet been floristically sampled, additional taxonomic novelties and new records are still expected in the future.